Knowledge science, engineering and management : 12th international conference, KSEM 2019, Athens, Greece, August 28-30, 2019 : proceedings.: 12th international conference, KSEM 2019, Athens, Greece, August 28-30, 2019 : proceedings. Part I ([2019]) - Unknown
No abstract available